2000
DOI: 10.1055/s-2000-8541
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of Three Saponins Isolated from Ivy, α-Hederin, β-Hederin and Hederacolchiside A1, as Compared to Their Action on Mammalian Cells Cultured in Vitro

Abstract: The in vitro antileishmanial activity of three saponins isolated from ivy, alpha-hederin, beta-hederin and hederacolchiside A1, was investigated on Leishmania infantum. The assessment of possible targets (membrane integrity, membrane potential, DNA synthesis and protein content) was performed in both Leishmania promastigotes and human monocytes (THP1 cells). Results observed in Leishmania showed that the saponins exhibited a strong antiproliferative activity on all stages of development of the parasite by alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 8 publications
(9 reference statements)
1
59
0
2
Order By: Relevance
“…Glycosides were inactive however; as previously reported most cytotoxic natural compounds do not belong to glycosides except for the cytotoxic saponin acting on cellular membranes. 15,16) In general, hydrophilic compounds with sugar moieties are hardly permeable to the cellular membranes. 17) Tectorigenin induced differentiation into granulocytes and/or monocytes/macrophages, as assessed by NBT reduction, latex beads phagocytic activity and CD14 and CD66b antigen expression, and by apoptosis, as assessed by increase in hypodiploid population and DNA ladder formation, of human promyelocytic leukemia HL-60 cells less effectively than genistein.…”
Section: Discussionmentioning
confidence: 99%
“…Glycosides were inactive however; as previously reported most cytotoxic natural compounds do not belong to glycosides except for the cytotoxic saponin acting on cellular membranes. 15,16) In general, hydrophilic compounds with sugar moieties are hardly permeable to the cellular membranes. 17) Tectorigenin induced differentiation into granulocytes and/or monocytes/macrophages, as assessed by NBT reduction, latex beads phagocytic activity and CD14 and CD66b antigen expression, and by apoptosis, as assessed by increase in hypodiploid population and DNA ladder formation, of human promyelocytic leukemia HL-60 cells less effectively than genistein.…”
Section: Discussionmentioning
confidence: 99%
“…Saponin not only has stimulatory effects on the components of specific immunity, but also presents some non-specific immune reactions such as inflammation (de Oliveira et al, 2001;Haridas et al, 2001) and monocyte proliferation (Delmas et al, 2000;Yui et al, 2001). …”
Section: Effects On Immune Systemmentioning
confidence: 99%
“…4) The antileishmanial activity of a-hederin, b-hederin and hederacolchiside A 1 in association with Pentamidine and Amphotericin B showed that subtoxic concentrations of these saponins enhance the efficiency of Pentamidine and Amphotericin B on the promastigote and the amastigote forms of the parasites. 5,6) Hederacolchiside A 1 was strongly cytotoxic against malignant melanoma M 4 Beu (IC 50 ϭ5 mM). 7) This saponin exhibits a preferential cytotoxicity on pigmented melanoma cells and interacts specifically with melanin.…”
mentioning
confidence: 99%